"Here we go again": the inspection of collagen extraction protocols for 14C dating and palaeodietary analysis. Issue 1 (1st January 2021) - Talamo, Sahra; Fewlass, Helen; Maria, Raquel; Jaouen, Klervia
ABSTRACT: Archaeological bone collagen is highly useful for radiocarbon ( 14 C) dating and palaeodietary reconstruction. However, collagen preservation and carbon contamination are essential considerations when extracting collagen, becoming especially crucial close to the limit of the method (50, 000 years before present = BP). Strong progress has been achieved in the past two decades by 14 C and stable isotopic laboratories in removing contamination from archaeological bones, but different pretreatment protocols have been proven to produce varying results. Here we compare three collagen extraction protocols used for palaeodietary studies and 14 C dating, considering collagen yield, elemental and stable isotopic data, FTIR analysis, and 14 C dates. We focus on the impact of ultrafiltration on the yield and quality of the extracted material. The results again underline the importance of rigorous decontamination methods to gain accurate 14 C dates and demonstrate that different protocols have significant effects on the quality and yield of extracted collagen.